2023
DOI: 10.1111/1753-0407.13439
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of nattokinase against microvasculopathy and neuroinflammation in diabetic retinopathy

Abstract: AimsDiabetic retinopathy (DR) is a significant global public health concern. Alternative, safe, and cost‐effective pharmacologic approaches are warranted. We aimed to investigate the therapeutic potential of nattokinase (NK) for early DR and the underlying molecular mechanism.MethodsA mouse model of diabetes induced by streptozotocin was utilized and NK was administered via intravitreal injection. Microvascular abnormities were evaluated by examining the leakage from blood–retinal barrier dysfunction and loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In a murine model of oxygen-induced retinal pathology, nattokinase attenuates neuroinflammation and inhibits pathological neovascularization by activating the Nrf2/HO-1 signaling pathway and modulating neuroglial activation [45]. For diabetic macular edema, commonly employed treatments involve injections of anti-vascular endothelial growth factor agents or corticosteroids, but there are still side effects such as drug resistance, macular ischemia, and disease recurrence [44,47,48]. Maintaining the integrity of the blood-retinal barrier (BRB) is fundamental in treating DR. Huang et al [47] demonstrated that nattokinase interferes with downstream signaling by inhibiting the expression of high-mobility group protein 1, thereby enhancing BRB function.…”
Section: Antiretinopathy Effect Of Nattokinasementioning
confidence: 99%
See 1 more Smart Citation
“…In a murine model of oxygen-induced retinal pathology, nattokinase attenuates neuroinflammation and inhibits pathological neovascularization by activating the Nrf2/HO-1 signaling pathway and modulating neuroglial activation [45]. For diabetic macular edema, commonly employed treatments involve injections of anti-vascular endothelial growth factor agents or corticosteroids, but there are still side effects such as drug resistance, macular ischemia, and disease recurrence [44,47,48]. Maintaining the integrity of the blood-retinal barrier (BRB) is fundamental in treating DR. Huang et al [47] demonstrated that nattokinase interferes with downstream signaling by inhibiting the expression of high-mobility group protein 1, thereby enhancing BRB function.…”
Section: Antiretinopathy Effect Of Nattokinasementioning
confidence: 99%
“…For diabetic macular edema, commonly employed treatments involve injections of anti-vascular endothelial growth factor agents or corticosteroids, but there are still side effects such as drug resistance, macular ischemia, and disease recurrence [44,47,48]. Maintaining the integrity of the blood-retinal barrier (BRB) is fundamental in treating DR. Huang et al [47] demonstrated that nattokinase interferes with downstream signaling by inhibiting the expression of high-mobility group protein 1, thereby enhancing BRB function. This heralds the potential of nattokinase as a prospective alternative medication for treating diabetic retinal pathologies.…”
Section: Antiretinopathy Effect Of Nattokinasementioning
confidence: 99%